Use of response surface methodology in characterization of properties of recycled high density polyethylene/ground tire rubber compositions - Formela, K.; Bogucki, M. (Polimery, 2014)
Searching for new ways to utilize rubber and polymer waste has been the focus of many studies conducted by research centers and companies worldwide. In this study, the influence of extrusion conditions on the properties of thermoplastic compositions containing post-production recycled high density polyethylene (PE-HD) and ground tire rubber (GTR) at 50:50 mass ratio was examined. Response Surface Methodology (RSM) was used to determine the effects of the barrel temperature (160—240 °C), screw speed (250—650 rpm) and feed rate of extrusion (1—2.5 kg/h) on the quality of the obtained products. Empirical models for determining the relationship between extrusion conditions, mechanical properties and the mass flow rate of obtained thermoplastic compositions were developed. It has been determined that tensile strength, elongation at break, hardness and the mass flow rate of thermoplastic compositions depend mainly on the barrel temperature. Properties of PE-HD/GTR blends deteriorated with increased barrel temperature, which was due to degradation of polyethylene and reclaiming of ground tire rubber. In studied extrusion conditions the influence of screw speed and feed rate on the properties of recycled high density polyethylene/ground tire rubber compositions was negligible.